Digital Literacy And Self-Control As Predictors Of Students’ Media Ethics At SMP Negeri 3 Pekalongan - Chusnul Chotimah; Yulis Sutiani; Mastora; Muhammad Alfi Syahrin (Al-Hikmah: International Journal of Islamic Studies, 2026)
The rapid development of digital transformation has significantly influenced students’ behavior in using social media and digital technology. The increasing occurrence of unethical digital communication, cyberbullying, hoax dissemination, and impulsive behavior on social media highlights the importance of strengthening digital literacy and self-control in shaping students’ media ethics. This study aimed to analyze the influence of digital literacy and self-control on students’ media ethics at SMP Negeri 3 Pekalongan. This study employed a quantitative approach with a correlational research design. The population consisted of students actively using digital media, with 92 respondents selected through proportional random sampling using the Slovin formula. Data were collected using a Likert-scale questionnaire and analyzed using IBM SPSS Statistics version 26 through classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The findings revealed that digital literacy and self-control had a positive and significant influence on students’ media ethics both partially and simultaneously. The coefficient of determination value of 0.525 indicated that both variables contributed 52.5% to students’ media ethics, while the remaining percentage was influenced by other variables outside the study. This study emphasizes that strengthening digital literacy and self-control is an essential strategy in developing a healthy, ethical, and responsible digital culture among students in the era of digital transformation.